2016
DOI: 10.1111/risa.12611
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Forest Management Strategy on Carbon Storage and Revenue in Western Washington: A Probabilistic Simulation of Tradeoffs

Abstract: The objectives of this study are to understand tradeoffs between forest carbon and timber values, and evaluate the impact of uncertainty in improved forest management (IFM) carbon offset projects to improve forest management decisions. The study uses probabilistic simulation of uncertainty in financial risk for three management scenarios (clearcutting in 45- and 65-year rotations and no harvest) under three carbon price schemes (historic voluntary market prices, cap and trade, and carbon prices set to equal ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…This integrated approach is a core tenet of management in the era of the blue economy (Klinger et al, 2018), yet multi-faceted approaches have yet to be developed and adopted (Link et al, 2018). Some have argued that monetizing ecological benefits, e.g., by expressing them in the consistent unit of dollars, makes it possible to quantify trade-offs between economic and ecological considerations (Chan et al, 2012;Fischer et al, 2016). Broader use of combined approaches include ecosystem services (Chan et al, 2012), using ecological and economic objectives in decision frameworks (Cullen et al, 2007;Fischer et al, 2016) and factoring human behavior into scenario analyses (Wilen et al, 2002;van Putten et al, 2012).…”
Section: What Is Ecological Risk Assessment How Is It Used and How Imentioning
confidence: 99%
See 1 more Smart Citation
“…This integrated approach is a core tenet of management in the era of the blue economy (Klinger et al, 2018), yet multi-faceted approaches have yet to be developed and adopted (Link et al, 2018). Some have argued that monetizing ecological benefits, e.g., by expressing them in the consistent unit of dollars, makes it possible to quantify trade-offs between economic and ecological considerations (Chan et al, 2012;Fischer et al, 2016). Broader use of combined approaches include ecosystem services (Chan et al, 2012), using ecological and economic objectives in decision frameworks (Cullen et al, 2007;Fischer et al, 2016) and factoring human behavior into scenario analyses (Wilen et al, 2002;van Putten et al, 2012).…”
Section: What Is Ecological Risk Assessment How Is It Used and How Imentioning
confidence: 99%
“…Some have argued that monetizing ecological benefits, e.g., by expressing them in the consistent unit of dollars, makes it possible to quantify trade-offs between economic and ecological considerations (Chan et al, 2012;Fischer et al, 2016). Broader use of combined approaches include ecosystem services (Chan et al, 2012), using ecological and economic objectives in decision frameworks (Cullen et al, 2007;Fischer et al, 2016) and factoring human behavior into scenario analyses (Wilen et al, 2002;van Putten et al, 2012). However, some economists have argued that economic considerations are frequently relegated to the cost-benefit factors used in decision-making, post hoc and separate from risk assessment (Williams and Thompson, 2004;Hoffmann, 2011).…”
Section: What Is Ecological Risk Assessment How Is It Used and How Imentioning
confidence: 99%
“…A variety of long-term field trials and simulation studies have demonstrated an opportunity for long-term timber supply to be increased by the extension of rotation ages closer to the culmination of Mean Annual Increment (MAI) of timber volume growth, and that the integration of commercial thinning may extend the culmination of MAI further into substantially older ages than current common practice [11][12][13][14][15][16]. The extension of rotation ages is also well-established as a means to increase average carbon storage in the forest system and is a common component in forest carbon policies and research [6,[17][18][19][20][21][22]. Previous work investigating the potential for carbon sequestration incentives to support the extension of rotation ages have specifically identified the coastal forests of the Pacific Northwest possessing unrivaled sequestration potential under a variety of carbon accounting approaches [17].…”
Section: The Productivity and Management Of Coastal Douglas-fir Forestsmentioning
confidence: 99%
“…Studies intended to be policy-or management-relevant using FVS without describing how they calibrated or validated the model may be vulnerable to large errors, a vulnerability that may be particularly concerning if climate change factors are integrated into FVS projections where little to no independent validation data may be available. For example, although forest carbon offset programs often impose substantial costs to minimize the potential variability or error in field measurement, they tend to ignore much larger sources of variability associated with the use of growth-and-yield models over a century-scale timeframe, whether or not climate change is acknowledged [21].…”
Section: Fundamental Importance Of Fvs Calibrationmentioning
confidence: 99%
See 1 more Smart Citation